Loss of the Tectorial Membrane Protein CEACAM16 Enhances Spontaneous, Stimulus-Frequency, and Transiently Evoked Otoacoustic Emissions - Cheatham, Mary Ann (Society for Neuroscience, 2014)
α-Tectorin (TECTA), β-tectorin (TECTB), and carcinoembryonic antigen-related cell adhesion molecule 16 (CEACAM) are secreted glycoproteins that are present in the tectorial membrane (TM), an extracellular structure overlying the hearing organ of the inner ear, the organ of Corti. Previous studies have shown that TECTA and TECTB are both required for formation of the striated-sheet matrix within which collagen fibrils of the TM are imbedded and that CEACAM16 interacts with TECTA. To learn more about the structural and functional significance of CEACAM16, we created a Ceacam16-null mutant mouse. In the absence of CEACAM16, TECTB levels are reduced, a clearly defined striated-sheet matrix does not develop, and Hensen's stripe, a prominent feature in the basal two-thirds of the TM in WT mice, is absent. CEACAM16 is also shown to interact with TECTB, indicating that it may stabilize interactions between TECTA and TECTB. Although brain-stem evoked responses and distortion product otoacoustic emissions are, for most frequencies, normal in young mice lacking CEACAM16, stimulus-frequency and transiently evoked emissions are larger. We also observed spontaneous otoacoustic emissions (SOAEs) in 70% of the homozygous mice. This incidence is remarkable considering that <3% of WT controls have SOAEs. The predominance of SOAEs >15 kHz correlates with the loss of Hensen's stripe. Results from mice lacking CEACAM16 are consistent with the idea that the organ of Corti evolved to maximize the gain of the cochlear amplifier while preventing large oscillations. Changes in TM structure appear to influence the balance between energy generation and dissipation such that the system becomes unstable.